Conferring fluorescence tracking function to polyphenylene sulfide by embedding the pyrene into the backbone at the molecular level: Design and synthesis. (10th December 2021) - Yan, Da-Wei; Li, Xiao-Dan; Li, Peng-Cheng; Tang, Wan-Li; Ren, Hao-Hao; Yan, Yong-Gang
Abstract: Morphological changes and damage degrees of PPS can be tracked and detected by fluorescence during service. However, the functionalization of the main chain of PPS is limited. To explore its luminescent properties for fluorescence tracking, 1, 6-dibromopyrene and 1, 3, 6, 8-tetrabromopyrene were employed to construct Dbp-PPS (Dibromopyrene-PPS) and Tbp-PPS (Tetrabromopyrene-PPS) with fluorescence tracking, respectively. These two sets of copolymers were systematically designed, synthesized, and characterized by Uv–Vis, PL, FT-IR, TGA, DSC, and XRD. To sum up, both Dbp-PPS and Tbp-PPS displayed visible fluorescence. UV–vis spectra showed an absorption maximum at λabs = 262–411 nm. PL spectra demonstrated emission maximum at λem = 450–545 nm. Particularly, 0.25%Dbp-PPS emitted the most intense blue fluorescence with the emission maximum at 450 nm and the absolute quantum yield of Φf = 0.08. The fluorescence decay lifetime of 0.25%Dbp-PPS comprised two components with lifetimes of 0.43 and 1.17 ns, implying the formation of excimer. The IR and XRD spectra of Dbp-PPS and Tbp-PPS were in line with those of PPS. TGA measurements illustrated that introducing pyrene into PPS is favorable for improving thermal stability. The DSC analysis indicated their melting temperature ranged from 260.9 to 280.4 °C and Dbp-PPS exhibited a little better melting point (279.4–280.4 °C) than neat-PPS (278.4 °C). Meanwhile, the resultant copolymers possessed a flexural strength of 31.0–101.5 MPa and tensile strength of 69.2–96.7 MPa. Both the flexural and tensile strengths of only 0.25%Dbp-PPS (101.5 and 86.8 Mpa) were higher than that of neat-PPS (95.1 and 84.3 Mpa). Imparting the pyrene unit into the PPS backbone is an effective method to give the PPS fluorescence tracking function for inspecting or tracking the polymer during their application and keep the original high performance of the PPS. Importantly, the systematic studies for pyrene-containing PPS in the current work provide a practical polymer tracking strategy suitable for other aromatic polymers such as poly (ether ether ketone), poly (ether sulfone). Graphical abstract: Image 1 Highlights: Polyphenylene sulfide with ultraviolet and fluorescent function is developed. Photophysical properties depend on the content and structure of pyrene. The copolymers combine excellent performance with tracking function.